Perancangan Baru Interior Concert Hall Pada Orchestra Music Community Center Bandung Dengan Pendekatan Akustik - Herning Roso Wulandari, Sarah; Nur Sheha Gunawan, Ahmad; Bayu Perdana, Aditya (Telkom University, 2024)
Orchestral music performances generally rely on original sound without the aid of loudspeakers, so it is very important to pay attention to the acoustics of the performance space. The interior design of a performance space, especially for orchestral music, must have good acoustics so that the sound quality produced is optimal and can be enjoyed by the audience. However, performance halls often experience acoustic defects that impact the quality of musical performances. To overcome this, careful acoustic planning is needed so that the performer can convey the music optimally and the audience can enjoy every note clearly. In addition, performance halls must comply with government standards in providing safe and comfortable facilities for users, so that the viewing experience is better. Keywords: interior, performance space, orchestra, acoustics, standard